Arterio-VENouS Intra Subject agreement for blood gases within intensive care: The AVENSIS study. (February 2020) - Nanjayya, Vinodh B; McCracken, Phoebe; Vallance, Shirley; Board, Jasmin; Kelly, Patrick J; Schneider, Hans G; Pilcher, David; Garner, Daniel J
Background: In critically ill patients, who require multiple blood gas assessments, agreement between arterial and venous blood gas values for pH and partial pressure of carbon dioxide, is not clear. Good agreement would mean that venous values could be used to assess ventilation and metabolic status of patients in intensive care unit. Methods: All adult patients admitted to Alfred intensive care unit, Melbourne, from February 2013 to January 2014, who were likely to have arterial and central venous lines for three days, were enrolled. Patients on extra-corporeal life support and pregnant women were excluded. After enrolment, near simultaneous arterial and central venous sampling and analysis were performed at least once per nursing shift till the lines were removed or the patient died. Bland-Altman analysis for repeated measures was performed to assess the agreement between arterio-venous pH and partial pressure of carbon dioxide. Results: A total of 394 paired blood gas analyses were performed from 59 participants. The median (IQR) number of samples per patient was 6 (5–9) with the median (IQR) sampling interval 9.4 (5.2–18.5) h. The mean bias for pH was + 0.036 with 95% limits of agreement ranging from − 0.005 to + 0.078. For partial pressure of carbon dioxide, the values were −2.58 and −10.43 to + 5.27 mmHg, respectively. Conclusions: The arterio-venous agreement for pH in intensive care unit patients appears to be acceptable. However, the agreement for partial pressure of carbon dioxide was poor.